UPAYA MENINGKATKAN PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI MELALUI BERMAIN PERAN - Khadijah; Mutiara Alya Hasyim; Fitrah Nasution (CV. ADIBA AISHA AMIRA, 2024)
Based on the results and discussions carried out by researchers, it was concluded that role-playing activities could improve the social-emotional abilities of group B children at Ananda Junior Kindergarten, Tampan Pekanbaru District. This can be proven by the increase in children's social emotional abilities that has been achieved, which can be seen from the implementation of actions in cycle I to the completion of actions in cycle II and researchers provide motivation to children and gifts as encouragement and appreciation for the children's efforts in carry out role playing activities well and get maximum results. The social emotional abilities of play group children increased after the researchers carried out actions from cycle I to cycle II which were carried out through several stages and processes including a) the author told the story b) then the children were asked to carry out role playing activities by following the storyline that had been designed as well as possible. and as much as possible.